Mathematics

Question

Which formula below gives the average rate of change of the function z(x) = -6x^2 + 3 on the interval -1≤x≤2?

2 Answer

  • z(2) - z(-1)
    -------------
      2 - (-1)

    = (-6(2)^2 + 3 ) - ( -6(-1)^2 + 3
    -----------------------------------------
                        3

    =  ( -21 - (-3))  / 3
    = -18 / 3
    = -6

  • Answer: [tex]\dfrac{z(2)-z(1)}{2-(-1)}[/tex]

    Step-by-step explanation:

    The average rate of a function f(x) is interval [a,b] is given by :-

    [tex]\dfrac{f(b)-f(a)}{b-a}[/tex]

    The given function: [tex]z(x)=-6x^2+3[/tex]

    Interval : [-1,2]

    Then using the above general formula , the average rate of change of the function z(x) = -6x^2 + 3 on the interval -1≤x≤2 is given by :-

    [tex]\dfrac{z(2)-z(1)}{2-(-1)}[/tex]

NEWS TODAY